Thigh Circumference and Risk of All-Cause, Cardiovascular and Cerebrovascular Mortality: A Cohort Study - Chen, Chao-lei (Risk Manag Healthc Policy, 2020)
PURPOSE: The relationship between thigh circumference and all-cause and cause-specific mortality has not been consistent. We aimed to examine how thigh circumference associates with all-cause, cardiovascular, and cerebrovascular mortality among US adults. PATIENTS AND METHODS: This cohort study included 19,885 US adults who participated in the 1999–2006 National Health and Nutrition Examination Survey (NHANES) with thigh circumference being measured at baseline, and survival status was ascertained until 31 December 2015. We used Cox proportional hazards models to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CI) for mortality according to thigh circumference in quartiles. Kaplan–Meier survival curve and restricted cubic spline regression were performed to evaluate the prospective association. Finally, subgroup analyses by age, gender, body mass index (BMI), and medical history at baseline were conducted. RESULTS: During a median follow-up of 11.9 years, 3513 cases of death, 432 death cases due to cardiovascular disease, and 143 death cases due to cerebrovascular disease have occurred. Multivariate Cox regression indicated that every 1cm increase in thigh circumference was related to 4% and 6% decreased risk of all-cause mortality and cardiovascular mortality, respectively. Compared to the reference group, the highest quartile of thigh circumference significantly decreased all-cause mortality by 21% (HR 0.79, 95% CI 0.62–1.00, P<0.05). However, the association of thigh circumference with cerebrovascular mortality was not significant. BMI was a significant effect modifier among individuals with a BMI of less than 25 kg/m(2) (P<0.0001). CONCLUSION: A low thigh circumference appears to be associated with increased risk of all-cause and cardiovascular mortality, but not cerebrovascular mortality.